Korelasi Empirik antara Kecepatan Gelombang Permukaan terhadap Kepadatan dan Kekakuan pada Campuran Laston â WC - Rosyidi, Sri Atmaja P; Ariani, Indra; Djaha, Siti Isnaini K (Jurnal Semesta Teknika, 2014)
Density and stiffness of asphaltic mixture are important parameter used for pavement design and construction. These parameter measure the required thickness of pavement.The aim of this study is to investigate the empirical relationship between pavement density and stiffness of Asphalt Concrete-Wearing Course (AC-WC) and surface wave velocity. Surface wave velocity is obtained from the seismic test set up in laboratory. A high frequency of impact source is employed in order to produce the high frequency waves propagating in mixture samples.The wave displacement is measured by accelerometer receivers connected to the computer for signal processing and spectrum analysis. In this study, AC-WC mixture is prepared with 35Ã,50Ã, 75Ã and 100Ã blows for providing sample with different density. From the results, it shows that the surface wave velocity is able to detect the various density of samples. Higher density of sample produces higher velocity and vice versa. Some empirical correlations between surface wave velocity with density and stiffness are also produced with significant statistical measures. This study shows the surface wave velocity is potential parameter employed for mixture assessment in pavement design and evaluation.Â